Permu-Nation Fiesta in Developing Math Skills of Grade 10 Students in Public Secondary Schools - Concepcion, Rio (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the effectiveness of the Permu-nation Fiesta Learning Activity Sheet as a contextualized instructional intervention for improving the numeracy skills of Grade 10 students in a public secondary school in the Ligao City Division during the school year 2024–2025. The study was anchored on Behavioral Learning Theory, Cognitive Learning Theory, and Closed Gap Learning Theory, which emphasize reinforcement, cognitive processing, and targeted intervention in addressing learning gaps. Using an experimental pre-test and post-test control group design, the study involved 80 Grade 10 students randomly assigned into experimental and control groups, with 40 students in each group, and five mathematics teachers who served as jurors in evaluating the supplementary learning material. Research instruments included a 20-item pre-test and post-test, juror validation sheets, and the Permu-nation Fiesta Learning Activity Sheet. Data were analyzed using frequency count, percentage, weighted mean, arithmetic mean, and z-test for two sample means. Findings revealed that both groups had very low mastery in numeracy skills during the pre-test. After the implementation of contextualized learning activities, both groups improved, but the experimental group showed higher post-test performance, attaining an overall mean of 83.75 compared with 60.25 for the control group. The computed z-value of 6.60, which exceeded the tabular value of 1.96 at the 0.05 level of significance, confirmed a significant difference between the groups. The supplementary learning activity sheet developed in the study was also rated excellent, with a weighted mean of 3.87. The study concluded that the Permu-nation Fiesta Learning Activity Sheet effectively enhanced students’ numeracy skills and is a highly acceptable instructional material. It is recommended that teachers integrate contextualized and targeted numeracy interventions, collaborative learning strategies, and regular assessment practices in mathematics instruction. The study is primarily aligned with SDG 4: Quality Education by supporting improved numeracy and learning outcomes, and it also relates to SDG 8: Decent Work and Economic Growth through the development of competencies essential for future employability. Its sustainability impact lies in strengthening educational practice through contextualized instructional materials and supporting long-term institutional and socio-economic development by improving students’ mathematics competence.
Keywords: Contextualized learning; Grade 10; Learning activity sheet; Numeracy skills; Permutation; Post-test; Pre-test